GEOCHEMICAL EVALUATION OF GROUNDWATER QUALITY IN NEWCASTLE, KWAZULU-NATAL, SOUTH AFRICA - Nolakana, P.; Siad, A.; Solomon, H. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Hydrogeochemical investigations were carried out in Newcastle, in the KwaZulu-Natal province of South Africa to identify the major geochemical processes that control groundwater chemistry. 31 samples were collected and analysed for Magnesium (Mg2+), Calcium (Ca2+), Sodium (Na+), Potassium (K+), Chloride (Cl-), Sulfate (SO42-), Bicarbonate (HCO3-), Nitrate (NO3-), Fluoride (F-), pH, TDS and EC. Classical hydro-chemical methods; facies analysis and major ion analysis were used to further understand the composition controlling processes. It was inferred from the hydro-chemical facies, major ion scatter plots that the major process affecting the groundwater chemistry in the area is rock-water interaction. The ionic concentration is due to silicate weathering, carbonate weathering and ion exchange processes.